2019
DOI: 10.4236/jss.2019.75013
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Technical and Vocational Education and Training and Entrepreneurship Education to Address Unemployment in Lusaka Province, Zambia

Abstract: The aim of this study was to highlight how a combination of TVET and entrepreneurship education can be harnessed to address the problem of unemployment as well as underutilisation of human resources, in Lusaka Province, Zambia, to foster sustainable social economic development. A questionnaire was administered to TVET students. A representative sample of 480 respondents was targeted. Interview respondents included TVET instructors, TVET administrators, TVET government officers, Industry experts and parents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…This is in agreement with the assertion of Osuala (2004) that the problems of funding TVET programmes were because of inadequate budgetary provisions, the Federal Government being the sole funding, brain drain of highly qualified lecturers, lack of adequate classrooms and staff offices, and lack of teaching and learning equipment. The finding of this study is in line with the earlier findings by Mubanga, Hock, Karim and Mulenga (2019) who reported that lack of funding or inadequate funding were the causes of poorly resourced vocational institutions leading to inadequate tools, equipment, shortage of teaching materials in vocational schools and low motivation among the teaching staff.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with the assertion of Osuala (2004) that the problems of funding TVET programmes were because of inadequate budgetary provisions, the Federal Government being the sole funding, brain drain of highly qualified lecturers, lack of adequate classrooms and staff offices, and lack of teaching and learning equipment. The finding of this study is in line with the earlier findings by Mubanga, Hock, Karim and Mulenga (2019) who reported that lack of funding or inadequate funding were the causes of poorly resourced vocational institutions leading to inadequate tools, equipment, shortage of teaching materials in vocational schools and low motivation among the teaching staff.…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…Ep-Nuffic (2016) remarked that in Indonesia, South Africa, Chili, Kenya, Colombia among others, alumni associations contributed significantly to the funding of TVET in 2015 to support the finding of this study. Mubanga, Hock, Karim and Mulenga (2019) asserted that some of the most appropriate sources of funding TVET and entrepreneurship education are: government grants, student fees (households), private sector investments, company contributions (skill levies), employee contributions (payroll based), internally generated income from services offered by TVET training providers and regulation fees, external assistance in the form of donor grants/NGO contributions and cooperating partners' loans corroborates the findings of this study. In agreement with the findings of this study, Palmer (2019) stated that there needs to be greater awareness that countries do not just need sufficient and predictable revenue streams to fund training programmes, but perhaps just as importantly they need to have in place appropriate financing mechanisms that are themselves strongly linked to achieving reform policy objectives.…”
Section: Discussion Of Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…Vocational education and training (VET) is a method that focuses on learning and mastering certain procedures and is based on scientific notions [20], [30]. The name VET corresponds to the basic rules defined by UNESCO-UNEVOC [21], [31], [32] is a based on cognitive theory, with three theoretical viewpoints underpinning the curriculum and teaching practices [33].…”
Section: Vet Adoption and Approachmentioning
confidence: 99%
“…Marginalized people have less or no access to education and employment opportunities ( Cohan, 2012 ). Supporting the younger generation in starting their businesses is a strategy to combat unemployment ( Ghio et al, 2016 ; Mubanga et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%